An Examination into Role of Education in Promoting Cybernetic Mode: An Effective Learning Tool: Exploring the Impact of Education on the Adoption of Cybernetic Payment Modes (Journal of Advances and Scholarly Researches in Allied Education, 2018)
The expanding utilization of the web, versatile use of mobile phones, and government endeavors combined with the widespread use of cybernetic payment modes, etc. have shifted the consumer base towards the use of more and more cybernetic modes. Cybernatic mode has revolutionized retailing by making consumers buying different products from all over the world. In the last decade, India has witnessed huge growth in the use of mobile phones in the digital India era. Cybernatic mode is a type of e-commerce transaction to include electronic payment for buying products and services like Paytm, Free charge, Google pay, Mobikwik, etc. As technology is developing, the devices used for transacting electronically are rapidly increasing especially after demonetization. The complete adoption of cybernetic payment in developed economies is showing its ripple effect in developing economies as well.